Análise da DORT em operadores de caixas de supermercado: um estudo de caso - Ghisi, Marcos (2014)
Nowadays the diseases related with inappropriate and repetitive movements, are becoming endemic. Every day, more and more workers in many segments, are suffering with Repetitive Strain Injuries, and Work-related Musculoskeletal Disorders, also known in Brazil health laws as LER/DORT. The class of supermarket cashiers are no exception in this rule, and in many cases, presents disorders that are related with the actions and tasks of the work. Some supermarkets also disfavor the activity of these professionals, not offering suitable work station or appropriate EPI´s (Equipment for individual security). Thus, it seemed pertinent to the development of this study, in order to highlight the ergonomic problems, which can promote the emergence of LER/DORT diseases in supermarket cashiers. The research was developed from a case study, analyzing a supermarket in the city of Ampére/PR/Brazil, the results presented are produced by the observations made during regular business hours, on a Friday, day 06, when the peaks of clients are higher.